Effect Of Budget Deficit, Government expenditure and Foreign Direct Investment on Evonomics Growth ASEAN - Gayatri, Firna Dwi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
This study aims to analyze the effect of budget deficit, government spending and foreign direct investment on ASEAN economic growth in 2012-2021. The data used in this research is secondary data in the form of panel data from 2012-2021, sourced from the World Bank and Countryeconomy. In this study using a quantitative approach to panel data regression analysis. The results of this study indicate that the budget deficit variable has a positive but not significant effect on economic growth, the government expenditure variable has a significant positive effect on economic growth and foreign direct investment has a significant positive effect on economic growth in ASEAN countries in 2012-2021.Keywords: Budget Deficit, Government Expenditure, Foreign Direct Investment